CCVP CVOICE quick reference sheets - Wallace, Kevin, 1965- (Cisco Press, 2006)
A new edition of this title is available, ISBN-10: 1587058243 ISBN-13: 9781587058240 CCVP CVOICE Quick Reference Sheets (Digital Short Cut) Kevin Wallace, CCIE No. 7945 ISBN: 1-58705-322-5 As a final preparation tool providing a review of CVoice exam topics, the CCVP CVOICE Quick Reference Sheets complement official Cisco curriculum, other books, or other exam preparatory material. This digital Short Cut provides readers with detailed, graphical-based information, highlighting the key topics on the latest CVoice exam in a quick-review format. These fact-filled Quick Reference Sheets allow certification candidates to get all-important information at a glance, helping them to focus their study on areas of weakness and to enhance memory retention of important concepts. The CCVP certification recognizes a candidate's ability to create an IP telephony solution that is transparent, scalable, and manageable. Earning a CCVP certification validates a robust set of skills in implementing, operating, configuring, and troubleshooting a converged IP network. The certification content focuses on Cisco Systems Unified CallManager, quality of service (QoS), gateways, gatekeepers, IP phones, voice applications, and utilities on Cisco routers and Cisco Catalyst switches. The Cisco Voice over IP CVOICE exam assesses a candidate's knowledge of how to implement and support data and voice integration solutions at the network-access level. Topics covered include basic IP telephony operation, router configuration, support, troubleshooting, and integration with an existing public switched telephone network (PSTN). This Short Cut is derived from the print publication, Cisco IP Telephony Flash Cards and Exam Practice Pack, ISBN: 1-58720-128-3.